Strategic Management in Improving the Quality of Education in the Era of the Independent Curriculum - Hasnidar Hasnidar; Najmuddin Najmuddin; Sonny Muhammad Ikhsan Mangkuwinata (Widyagogik, 2026)
Improving educational quality during the Merdeka Curriculum era necessitates strategic, data-driven resource management to address policy shifts and student needs. This study aims to analyze school strategic management in enhancing educational quality through Data-Based Planning (DBP) at SMA Negeri 3 Unggul Sigli, Aceh. Employing a qualitative descriptive case study design, data were gathered via in-depth interviews, observations, and documentation involving the principal, teachers, and stakeholders. Data analysis followed the Miles and Huberman model, encompassing data condensation, display, and conclusion drawing. The findings reveal that strategic management is systematically executed through environmental scanning, formulation, implementation, and evaluation all integrated with Education Report Card (ERC) data. Environmental analysis identified strengths in teacher professionalism and academic culture, while formulation is conducted participatively through the Identification, Reflection, and Improvement (IRB) cycle. Strategy implementation focuses on numeracy-literacy programs, differentiated instruction, and the Profil Pelajar Pancasila project. Evaluation and control are performed continuously through routine monitoring and academic audits. The integration of DBP has significantly improved planning accuracy and instructional effectiveness, evidenced by an upward trend in the school’s ERC outcomes. This research concludes that DBP is not merely a technical tool but a strategic managerial practice that drives sustainable quality transformation. This study provides a novel framework for school leaders to transition from intuitive to evidence-based management within the Merdeka Curriculum ecosystem. For long-term impact, schools must consistently optimize data-driven governance to ensure academic resilience and institutional excellence.